Synthesizing the schemes of multifunctional measuring transduсers of the fluid parameters - Pistun, Yevhen; Matiko, Halyna; Krykh, Hanna; Matiko, Fedir (Eastern-European Journal of Enterprise Technologies, 2017)
A procedure for mathematical description of throttle matrices of various sizes in a form of graphs was developed which makes it possible to get all possible schemes with various measuring channels based on a throttle matrix of a certain size. By applying the elements of combinatorics, formulas were derived for finding the number of connections of throttle elements in the matrix, the number of all measuring channels, the number of all variants of construction of the measuring transducers based on a throttle matrix of a certain size. A generalized mathematical model of the throttle matrix was worked out which forms the basis for analysis of functional capabilities of the measuring transducer schemes. Principles of synthesis of schemes of multifunctional hydrodynamic measuring transducers based on throttle matrices were worked out. In accordance with the proposed principles, a throttle matrix of a certain size is chosen taking into account the number of measured parameters, fluid properties and requirements to the transducer accuracy or sensitivity. The throttle matrix is represented as a loaded graph with transform functions for each of the measuring channels. On the basis of the obtained graph and the general mathematical model of the matrix, a scheme and a mathematical model of the multifunctional measuring transducer of specified parameters of the fluid were synthesized. The obtained results enable algorithmization of the process of the measuring transducer scheme synthesis. The practical value of the performed studies consists in a synthesis of all possible schemes based on the throttle matrices with various measuring channels and a construction of measuring transducers with various functional capabilities and characteristics based on these matrices. By analyzing transform functions of each measuring channel of the throttle matrix of a certain size, one can choose an option for constructing a measuring transducer of one or more parameters with given functional capabilities and characteristics. The developed principles of synthesis of measuring schemes based on the throttle matrix can be used for construction of multifunctional hydrogasdynamic measuring transducers of physical and mechanical parameters of various media